The formation of peak-ring basins: working hypotheses and path forward in using observations to constrain models of impact-basin formation - Baker,DMH; Head,JW; Collins,GS; Potter,RWK (Icarus, 2015)
Impact basins provide windows into the crustal structure and stratigraphy of planetary bodies; however, interpreting the stratigraphic origin of basin materials requires an understanding of the processes controlling basin formation and morphology. Peak-ring basins (exhibiting a rim crest and single interior ring of peaks) provide important insight into the basin-formation process, as they are transitional between complex craters with central peaks and larger multi-ring basins. New image and altimetry data from the Lunar Reconnaissance Orbiter as well as a suite of remote sensing datasets have permitted a reassessment of the origin of lunar peak-ring basins. We synthesize morphometric, spectroscopic, and gravity observations of lunar peak-ring basins and describe two working hypotheses for the formation of peak rings that involve interactions between inward collapsing walls of the transient cavity and large central uplifts of the crust and mantle. Major facets of our observations are then compared and discussed in the context of numerical simulations of peak-ring basin formation in order to plot a course for future model refinement and development.